PENGGUNAAN MEDIA KONKRET DALAM PEMBELAJARAN UNTUK MENINGKATKAN KEAKTIFAN SISWA SEKOLAH DASAR: KAJIAN LITERATUR - Muhammad Fahrizal Ramadani; Nida Syafira; Nur Inayah; Rakhmadaniati Faznur; Ahmad Suriansyah; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This literature review analyzes the role of concrete media in improving the learning activeness of elementary school students. The study addresses the persistent issue of low participation resulting from teacher-centered instruction and insufficient use of tangible learning tools. Using research published between 2021 and 2025, the review synthesizes evidence demonstrating that concrete media enhance attention, motivation, and engagement by enabling students to observe, manipulate, and experience concepts directly. These media help simplify abstract ideas, strengthen conceptual understanding, and encourage students to participate more actively through questioning, discussion, and collaboration. The review also notes that success depends on teachers’ ability to design interactive, exploratory activities. Overall, the findings confirm that concrete media are an effective approach to fostering active, meaningful learning in elementary classrooms.